AUTODEZVOLTAREA BIBLIOTECARILOR – CONDIŢIE SINE QUA NON A EVOLUŢIEI PROFESIONALE - ŢURCAN, Conf. univ. dr. hab. , Universitatea de Stat din Moldova, Nelly (BIBLIOPOLIS, 2020)
The field of librarianship is ever expanding and changing, from exploding information technologies, to diverse groups of users with increasingly complex information needs. Library professionals need to be as savvy as the clients they serve, and the most productive and effective way for librarians to keep up with these changes is to seek out professional development opportunities. This paper seeks to address the changing trends of the library profession, including the changing nature of library and information science self-development as a method of continuing education, and to exemplify the importance and necessity of self-development for librarians. The paper presents several results of the survey regarding professional competences of librarians and continuing professional education that has been conducted in libraries of the Republic of Moldova.